Haplogroup T Is an Obesity Risk Factor: Mitochondrial DNA Haplotyping in a Morbid Obese Population from Southern Italy. (2nd July 2013) - Nardelli, Carmela; Labruna, Giuseppe; Liguori, Rosario; Mazzaccara, Cristina; Ferrigno, Maddalena; Capobianco, Valentina; Pezzuti, Massimo; Castaldo, Giuseppe; Farinaro, Eduardo; Contaldo, Franco; Buono, Pasqualina; Sacchetti, Lucia; et al.
Abstract : Mitochondrial DNA (mtDNA) haplogroups have been associated with the expression of mitochondrial-related diseases and with metabolic alterations, but their role has not yet been investigated in morbid obese Caucasian subjects. Therefore, we investigated the association between mitochondrial haplogroups and morbid obesity in patients from southern Italy. The mtDNA D-loop of morbid obese patients (n = 500 ; BMI > 40 kg/m 2 ) and controls (n = 216 ; BMI < 25 kg/m 2 ) was sequenced to determine the mtDNA haplogroups. The T and J haplogroup frequencies were higher and lower, respectively, in obese subjects than in controls. Women bearing haplogroup T or J had twice or half the risk of obesity. Binomial logistic regression analysis showed that haplogroup T and systolic blood pressure are risk factors for a high degree of morbid obesity, namely, BMI > 45 kg/m 2 and in fact together account for 8% of the BMI. In conclusion, our finding that haplogroup T increases the risk of obesity by about two-fold, suggests that, besides nuclear genome variations and environmental factors, the T haplogroup plays a role in morbid obesity in our study population from southern Italy.